2002
DOI: 10.1038/sj.bjc.6600321
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification and expression analysis of gastric cancer-associated genes

Abstract: Serological identification of tumour antigens by recombinant expression cloning has proved to be an effective strategy for the identification of cancer-associated genes having a relevance to cancer aetiology and progression, and for defining possible targets for immunotherapeutic intervention. In the present study we applied this technique to identify immunogenic proteins for gastric cancer that resulted in isolation of 14 distinct serum-reactive antigens. In order to evaluate their role in tumourigenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Granulin, a putative growth factor, was noted to be significantly overexpressed in carcinomas compared with adenomas. Previous studies of glioblastoma and gastric and ovarian cancers have also shown an up-regulation of this gene (27)(28)(29). Of the down-regulated genes, DUSP 1, which has known proliferation and differentiation functions, has been shown previously to be down-regulated in follicular carcinomas (17) and in advanced epithelial ovarian cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…Granulin, a putative growth factor, was noted to be significantly overexpressed in carcinomas compared with adenomas. Previous studies of glioblastoma and gastric and ovarian cancers have also shown an up-regulation of this gene (27)(28)(29). Of the down-regulated genes, DUSP 1, which has known proliferation and differentiation functions, has been shown previously to be down-regulated in follicular carcinomas (17) and in advanced epithelial ovarian cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…From a cancer standpoint, it is of interest to note that the mouse N-terminal acetyltransferase is implicated in vascular development (33)(34)(35) and therefore may play an active role in angiogenesis. The human orthologue, tubedown-100, also termed NATH or Ga19, has been shown to be implicated in transcription of the osteocalcin gene (36) and is overexpressed in papillary thyroid carcinoma (37) and gastric cancer (38). The role, if any, that ARD1 plays in these processes as a NAT-interacting partner remains unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…In breast carcinoma, it has been suggested that NUCB2 may be upregulated by estrogen and serve an important role in increased proliferative, migratory and invasive properties in MCF-7 and SK-BR-3 breast cancer cells (13). It has also been suggested in gastric carcinoma that NUCB2 is a candidate biomarker gene for cancer, which may be identified as a novel potential target for immunotherapeutic treatment (25). Furthermore, a study investigating ovarian epithelial carcinoma in 2013 by Xu et al (24) revealed a notable function of NUCB2/nesfatin-1, where it prevented proliferation in the human ovarian epithelial carcinoma HO-8910 cell line through apoptosis signaling, via the mechanistic target of rapamycin-RhoA/RhoA kinase signaling pathway, which serves an important role in cancer cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%